Analisis Framing Pemberitaan Persebaya Pasca Kongres PSSI 10 November 2016 pada Harian Surya dan Jawa Pos (Faculty of Communications Science, Dr. Soetomo University, 2017)
The purpose of this research is to know how newspaper Jawa Pos and Daily Surya in framing Persebaya Club Coverage after PSSI congress dated November 10, 2016, which void to acknowledge Persebaya status. Data collection techniques that researchers use in this study is Documentation. In this case the documented data is in the form of a collection of news texts from both the Surya and Jawa Pos newspapers dated 11 - 17 November 2016, Observation. This method is used to observe news related to Club News Persebaya After PSSI Congress. So the data observations conducted by the authors are daily newspaper Harian Surya and Jawa Pos, Data Classification. Based on the model of Zhongdang Pan and Gerald M.Kosicki, this research clarifies the facts based on a framing device that includes four large structures, which include syntactic, script, thematic, and rhetorical structures. Based on the result of research, show that both media of Jawa Pos and Harian Surya in telling news different from each other. In this case it encompasses the sources, opinions, writings, content and news images. Keywords: Framing Analysis, PSSI Congress, Harian Surya, Jawa Pos